Common Fixed Point Theorems for Weakly Contractions in Rectangular b-Metric Spaces with Supportive Applications - Hongyan Guan; Jianju Li; Yan Hao (Journal of Function Spaces)
In this manuscript, two new classes of generalized weakly contractions are introduced and common fixed point results concerning the new contractions are proved in the context of rectangular b-metric spaces. Also, some examples are included to present the validity of our theorems. As an application, we provide the existence and uniqueness of solution of an integral equation.